Partnered dance evokes greater intrinsic motivation than home exercise as therapeutic activity for chemotherapy-induced deficits: secondary results of a randomized, controlled clinical trial - Worthen-Chaudhari, Lise; Schnell, Patrick M.; Hackney, Madeleine E.; Lustberg, Maryam B. (Frontiers in Psychology, 2024)
Dance has been proposed to support superior intrinsic motivation over non-dance forms of therapeutic physical activity. However, this hypothesis has yet to be evaluated, empirically, particularly among populations living with neuropathology such as survivors of cancer with neurologic complications from chemotherapy treatment. Questions about motivation are relevant to clinical outcomes because motivation mediates neuroplasticity, and is mediated by embodied agency. To begin to investigate the relationships between personal motivation and neurophysiologic effects of dance-based intervention for healthy aging among populations with neurologic complications of cancer, we measured motivation using the Intrinsic Motivation Inventory, a validated patient-reported outcome from the psychological approach of Self Determination Theory. We assessed intrinsic motivation, extrinsic motivation, and satisfaction with intervention within a randomized controlled trial of dance versus exercise designed to alleviate symptoms of chemotherapy-induced impairment. Fifty-two survivors of breast cancer with chemotherapy-induced neuropathy diagnosis and sensorimotor functional deficits were randomized (1:1) to 8 weeks of partnered dance or home exercise, performed biweekly (NCT05114005; R21-AG068831). While satisfaction did not differ between interventions, intrinsic motivation was higher among participants randomized to dance than those randomized to exercise (p<0.0001 at all timepoints: 2 weeks, 4 weeks, 6 weeks, and 8 weeks of intervention), as was extrinsic motivation at 2 weeks (p = 0.04) and 8 weeks (p = 0.01). These data provide evidence that social dance is more motivating than the type of home exercise generally recommended as therapeutic physical activity. The results inform directions for future study of the effect of dance-based therapeutics on embodied agency, neuroplastic changes, and clinically-relevant neuropathic improvement.